An urban location service for vehicular area networks. (25th May 2018) - Nebbou, Tawfiq; Lehsaini, Mohamed; Fouchal, Hacène; Ayaida, Marwane
Summary: Position‐based routing, also called geographic routing, is widely recognised as an efficient routing approach for highly dynamic and mobile networks as vehicular ad hoc networks (VANETs). In this kind of networks, the high‐speed mobility of vehicles causes rapid changes on the network topology measured with vehicles density, limited‐time communication links, link failures, etc. In the meantime, the need of location service is a key issue; indeed, it will allow finding the position of a target node in order to reach it with a message. Some theoretical studies have proposed location services based on sharing nodes informations in different ways with hierarchy mechanism or with distribution mechanism or with centralization process. This paper proposes a location service deployed on RSUs (Road Side Units) for unicast routing over VANETs in urban environment. The proposed approach is able to measure the connectivity of a route. We propose then a new metric called Link Connectivity (LC) which measures this connectivity. Additionally, we have implemented our proposal using OMNET++ simulator and we have conducted extensive simulations with various scenarios to evaluate its scalability and robustness against frequent topology changes. As a conclusion, the proposed mechanism provides significant performance improvements in terms of packet delivery ratio, end‐to‐end delay, and overhead when it is compared to some other known proposals.